ANALYSIS OF FACTORS AFFECTING EFFECTIVE AND EFFICIENT ENGLISH LEARNING - RIKA SYAH MEWAH MUNTHE (LP2MTBM MAKARIOZ, 2021)
Analysis of factors that influence effective English learning. The writing method uses the library research method. From thediscussion, it can be concluded that there are two types of learning theories that influence further learning theories, namely thetheory of behaviorism and cognitivism. Based on these two theories, language learning activities can be successful(successful) if carried out with experience accompanied by a stimulus so that it produces a response as well as being givenreinforcement (award). The award in question does not have to be in the form of objects. Meanwhile, based on the theory ofcognitivism, humans learn by themselves because they see and hear. Therefore, language learning activities must providemore examples as well as direct application (application) by students. There are four aspects of language skills that becomethe reference for language learning in schools, namely listening skills (listening), speaking skills, reading skills and writingskills.